Research Using RSM, Optimal Solution of Parameters for Machining Inconel 718: Optimization of Cutting Parameters for Machining Inconel 718 Using RSM and Taguchi Methodology (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Inconel 718 is widely used in advanced technologies because of its special properties for engineering applications dependent on nickel. The processing of Inconel 718 is difficult and expensive because of its unique features. Current study seeks the optimization methodology of Taguchi to optimize cutting parameters with the Inconel 718 high-speed turning method. The results of the cermet tool are represented with the methodology for answer surface (RSM). The experimental strategy consists of core composite concepts (CCD). The response variables examined are surface ruggedness and flank wear. The test results showed that the proposed mathematical models could accurately characterize the performance metrics within the limits of the variables under study. The most important element affecting the surface roughness and wear of the flank is cutting pace. However, there are several considerations that make the success metrics secondary. A variance review checks the suitability of the prediction model.